Media Sosial: Sarana Pewartaan Iman Di Era Milenial - Marius Goo; Elisabet Hagisimijau (Sekolah Tinggi Katolik Touye Paapaa Deiyai, 2024)
God's revelation always requires a human response called faith. The development of faith is always faced with a real context. Faith in the millennial era must be a special concern of the faithful so that it is not crushed by the development of social media. Social media must be a means of proclaiming faith, not the other way around. Understanding social media and making it a means of proclaiming faith is very important and urgent especially for millennials, so that everyone becomes children of God and not children of the devil.